(untitled) (Anclajes, 2021)
The Latin American literature of the last thirty years is crossed by displacement of bodies through plots that do not have the stability of the social and cultural borders that shape the nation-state. In a society where the ideal of well-being, happiness and longevity acquires a political status, Rodolfo Fogwill’s latest novel, La introducción (2016) constitutes a formal inquiry into the new spatializations of culture and new mechanisms of subjectivation and control that emerge in the novel of our turn of the century as indexes of transformations of power and forms of exploitation without which 24/7 capitalism could not function.